Taggers: Marketing 4.0 and the case of TAG (Intercom - Brazilian Journal of Communication Sciences, 2023)
Marketing strategies evolve alongside new communication models led by digital platforms in an increasingly connected society. Currently, companies seek to relate to their customers based on emotional logic and recognition in relation to brands, surpassing only the rational aspects linked to products and services. In the wake of investigations linked to changes in marketing tactics, this article will address the concept and applications of Marketing 4.0 based on the business model led by the company TAG - Literary Experiences. To this end, the study analyzed the company’s official digital channels, with an emphasis on Facebook, Instagram, and mobile applications, based on content analysis. It is concluded that the company is focused on new customer relationship paradigms, creating ways of identifying with its target audience as the essence of its services, based on the new challenges proposed by Marketing 4.0.
Keywords: Marketing 4.0; Experience; Tag Books; Social media; Digital Platforms